KUASA BAHASA KESEPULUH FIRMAN: SUATU KAJIAN ANALISIS WACANA HISTORIS TERHADAP KELUARAN 20:1-17 - Wenas, Richo; Pandean, Mariam Lidia Mytty; Warouw, Maya Pinkan (Publisher: Bethel Press; Unit Penerbit: STT Bethel Indonesia Jakarta, 2025)
This article examines the Ten Commandments (Exodus 20:1–17) using the Discourse-Historical Approach (DHA) as developed by Ruth Wodak. The study aims to analyze how divine authority is constructed and legitimized both linguistically and theologically within the text, while also uncovering the social and theological implications of language use in shaping the moral and spiritual order of the faith community. The research employs a qualitative method with a literature-based approach. The findings reveal that the Ten Commandments function not merely as ethical imperatives but also as a discursive instrument for constructing social structures, legitimizing divine authority, and forming the collective identity of the people of Israel. Analysis of topical structure, discursive strategies, and linguistic features within the text confirms the role of language as a vehicle for establishing norms, authority, and the social world of believers. These insights contribute a new dimension to biblical theological studies through the lens of critical linguistic analysis.